Childbearing Age, Family Allowances, and Social Security. - Pestieau, Pierre; Ponthiere, Gregory (Southern Economic Journal, 2013)
Although the optimal public policy under an endogenous number of children has been widely studied, the optimal public intervention under an endogenous timing of births has remained largely unexplored. This paper examines the optimal family policy when the timing of births is chosen by individuals who differ as to how early fertility weakens future earnings. We analyze the design of a policy of family allowances and of public pensions in such a setting, under distinct informational environments. Endogenous childbearing ages is shown to affect the optimal policy through the redistribution across the earnings dimension and the internalization of fertility externalities. Contrary to common practice, children benefits differentiated according to the age of parents can be part of the optimal family policy. Our results are robust to introducing: (i) children as durable "goods"; (ii) education choices; (iii) varying total fertility.